NEW AND SIGNIFICANT ISLAND RECORDS, RANGE EXTENSIONS AND ELEVATIONAL EXTENSIONS OF BIRDS IN EASTERN SULAWESI, ITS NEARBY SATELLITES, AND TERNATE - Frank E Rheindt; Dewi M Prawiradilaga; Suparno; Hidayat Ashari; Peter R Wilton (Treubia, 2014)
The Wallacean Region continues to be widely unexplored even in such relatively well-known animal groups as birds (Aves). We report on the results of an ornithological expedition from late Nov 2013 through early Jan 2014 to eastern Sulawesi and a number of satellite islands (Togian, Peleng, Taliabu) as well as Ternate. The expedition targeted and succeeded with the collection of 7–10 bird taxa previously documented by us and other researchers but still undescribed to science. In this contribution, we provide details on numerous first records of bird species outside their previously known geographic or elevational ranges observed or otherwise recorded during this expedition. We also document what appears to be a genuinely new taxon, possibly at the species level of kingfisher from Sulawesi that has been overlooked by previous ornithologists. Our results underscore our fragmentary knowledge of the composition of the avifauna of eastern Indonesia, and demonstrate that there continues to be a high degree of cryptic, undescribed avian diversity on these islands more than a century and a half after they were visited by Alfred Russel Wallace and other collectors.